"The Future in the Past": Anarcho-primitivism and the Critique of Civilization Today. Issue 2 (2nd April 2020) - el-Ojeili, Chamsy; Taylor, Dylan
Abstract : This essay examines the core ideas and contemporary relevance of anarcho-primitivism, a current of ultra-leftist thought that flourished between the mid 1980s and mid 1990s. The influences of anarcho-primitivism can be traced to periods from the late nineteenth century to the Great War and from 1945 to the mid 1960s, with challenges to conventional leftism issued by thinkers such as Jacques Camatte. In place of a narrow criticism of capitalism and the modern state, anarcho-primitivism offers a wide-ranging critique of civilization. The utopian complement to this critique is to advocate a "future primitive" mode of being, reconciling with nature and reestablishing community. After considering critical issues with anarcho-primitivism, this essay examines how its themes have reappeared in more recent critical thought—as seen in the work of Derrick Jensen and Timothy Morton—and how these themes continue to raise important challenges against a hegemonic liberalism that emphasizes growth, competition, and individualism.